2015
DOI: 10.1039/c4mb00734d
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive gene and microRNA expression profiling reveals miR-206 inhibits MET in lung cancer metastasis

Abstract: MiRNAs associated with the metastasis of lung cancer remain largely unexplored. In this study, gene and miRNA expression profiling were performed to analyze the global expression of mRNAs and miRNAs in human high- and low-metastatic lung cancer cell strains. By developing an integrated bioinformatics analysis, six miRNAs (miR-424-3p, miR-450b-5p, miR-335-5p, miR-34a-5p, miR-302b-3p and miR-206) showed higher target gene degrees in the miRNA-gene network and might be potential metastasis-related miRNAs. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 48 publications
0
37
1
Order By: Relevance
“…Similar findings could also be seen in cancer cell line level, including osteosarcoma [22], prostate and colon cancer [23], colorectal cancer [24], renal cancer [25], and hemangioma [26]. In our study, we have found that up-regulation of miR-424-3p was markedly capable of suppressing the migration and invasion in NSCLC cells, which was in stark contrast with Chen et al finding that miR-424-3p was significantly upregulated in high metastatic NSCLC cells via integrated bioinformatics analysis [15]. However, our findings were entirely consistent with Wu et al showed that miR-424 could suppress invasion in bladder cancer [20].…”
Section: Discussioncontrasting
confidence: 94%
“…Similar findings could also be seen in cancer cell line level, including osteosarcoma [22], prostate and colon cancer [23], colorectal cancer [24], renal cancer [25], and hemangioma [26]. In our study, we have found that up-regulation of miR-424-3p was markedly capable of suppressing the migration and invasion in NSCLC cells, which was in stark contrast with Chen et al finding that miR-424-3p was significantly upregulated in high metastatic NSCLC cells via integrated bioinformatics analysis [15]. However, our findings were entirely consistent with Wu et al showed that miR-424 could suppress invasion in bladder cancer [20].…”
Section: Discussioncontrasting
confidence: 94%
“…miR‐1‐3p and miR‐206 have been identified as tumour suppressors in various human cancers, including lung cancer . Exogenous expression of these two miRNAs could significantly reduce cell motility and invasiveness .…”
Section: Resultsmentioning
confidence: 99%
“…miR-1-3p and miR-206 have been identified as tumour suppressors in various human cancers, including lung cancer. 6,12,17,18,23,24 Exogenous expression of these two miRNAs could significantly reduce cell motility and invasiveness. 25 In this study, we evaluated miR-1-3p and miR-206 expression in HGF stimulation of PC-9 and HCC827 cells.…”
Section: Pc-9 and Hcc827 Cell Lines (Both Harbouring Egfr Exon 19 Delmentioning
confidence: 99%
“…Previous evidence has demonstrated the association between aberrant MET signaling and medulloblastoma development (33,34). Previous studies have revealed that overexpressed miR-206 may inhibit MET in lung cancer (35,36), however the function of downregulated miR-206 in medulloblastoma is unknown. SREBF1 is a transcription factor, regulating lipogenesis, which is also involved in tumorigenesis (37).…”
Section: Discussionmentioning
confidence: 99%